Transformation Of Entrepreneurial Intention Through Entrepreneurship Education And Digital Literacy Among Students Of State Vocational Schools In Mojokerto City - Rahmawati, Rahmawati; Agus Hermawan; Agus Sumanto (International journal of technology and education research, 2025)
In the era of globalization, the ability to be an entrepreneur has become an important skill that supports the development of one's economic potential. This situation indicates the need for further investigation to understand the elements that can influence entrepreneurial intention. This study aims to explore the impact of entrepreneurship education on entrepreneurial intention through digital literacy and entrepreneurial attitude among vocational high school students in Mojokerto City. The research method used is the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Data analysis techniques use descriptive statistics. The results of the analysis show that: (1) There is a positive and significant effect of entrepreneurship education (X) on digital literacy (Z1), (2) There is a positive and significant effect of entrepreneurship education (X) on entrepreneurial attitudes (Z2), (3) There is a direct positive and significant effect of entrepreneurship education (X) on Entrepreneurial Intention (Y), (4) There is no positive and significant direct effect between the Digital Literacy (Z1) variable on Entrepreneurial Intention (Y), (5) There is a positive and significant direct effect of Entrepreneurial Attitude (Z2) on Entrepreneurial Intention (Y), (6) There is no direct positive and significant influence between Entrepreneurship Education (X) on Entrepreneurial Intention (Y) through Digital Literacy (Z1), (7) There is a direct positive and significant influence between Entrepreneurship Education (X1) on Entrepreneurial Intention (Y) through Entrepreneurial Attitude (Z2). The importance of this result lies in the synergy between education (academics), industry/digital world, government, and entrepreneurial communities so that entrepreneurial learning not only improves digital literacy but also truly shapes entrepreneurial attitudes that encourage entrepreneurial intent. These findings are expected to serve as a reference for schools and policymakers in developing entrepreneurship learning strategies that emphasize the formation of entrepreneurial attitudes, while also strengthening digital literacy to support an increase in the entrepreneurial intentions of vocational school students